The larvae of Silo chrisiammos Malicky 1984 and Lithax musaca Malicky 1972 (Trichoptera: Goeridae), including a key to the Goeridae larvae of the Eastern and Hellenic western Balkan regions - Waringer, Johann; Graf, Wolfram; Sipahiler, Füsun; Malicky, Hans (Zootaxa, 2017)
The paper gives a description of the hitherto unknown larvae of Silo chrisiammos Malicky 1984 and Lithax musaca Malicky 1972 (Trichoptera: Goeridae). Information on the morphology of the larvae is given and the most important diagnostic features are illustrated. In the context of published keys, both larvae belong to the group of goerid species with 6 mesonotal and 8 metanotal sclerites. Within this group, both species can be easily diagnosed by their unique pronotum morphology: The nose-like hump of S. chrisiammos descends stepwise posteriorly and stays clear of the caudal pronotal border, whereas in L. musaca the ridgelike hump descends gradually and touches the posterior pronotal border at center; in addition, in both species pronotal muscle attachment spots are not bordered by dark-pigmented dots. With respect to distribution, S. chrisiammos is a micro-endemic of the Greek Cyclades island of Andros whereas L. musaca is known from Anatolia, the European part of Turkey and Bulgaria. In addition, ecological characteristics are briefly discussed, and a key to the Goeridae larvae of European Ecoregions 6 and 7 (Hellenic western Balkan and Eastern Balkan regions) is included.